World Christianity as 'Human Universal Making' Activity: The Contribution of African Christian Potential. (August 2020) - Kaunda, Chammah J.
The study engages Alain Badiou's philosophical concept of 'immanent exception' to establish the special potential embedded in African Christianity for engendering human universal (Umuntu). It argues that African Christian experiences inform their interpretations of Jesus Christ as the answer to all human existential concerns. This approach forces them to 'exceed' in the locations and spaces of their imaginations of suffering by embracing ambivalent localizations (through a constant oscillation between local and un-local) in search to transcend, not escape, in thought and practice their negative realities. Thus, they transcend unitary Christian boundaries and integrates critical elements of African spiritual systems to build human universal within the paradigmatic universal humanity of Jesus. The study underlines that grasping African Christianity through immanent exception could contribute to empowering not only African Christians, but also world Christians to seek new ways of becoming human universal for global struggle against death dealing forces such as COVID-19. The study concludes by calling for the need to engage how World Christianity in its particularities is shaping life today and how local churches are participating in constructing what it means to be part of God's mission to build a human universal in active search for global justice.